Islam Nusantara Sebagai Manifestasi Nahdlatul Ulama (NU) dalam Mewujudkan Perdamaian - Munfaridah, Tuti (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
AbstractThe phenomenon is seen in today's society is the impression that; "Islam is a terrorist, bomb, loud, kill, covered and other labels that is contrary to the teachings of Islam itself be rahmatan li al-'alamaeen." Even in the Western world was antipathy to Islam so as to "hear" the word Islam alone horror and antipathy even hate.In such a condition that the term "Islam Nusantara" among leaders Nahdtlatul Ulama Ulama (NU). But the reality in society the term Islam Nusantara still very strange, even among radical Islam mengangggap "Islam Nusantara" is Islam perverted access all religions in Indonesia, or Islam "mix" of various religions in Indonesia, instead of pure Islam as taught by Prophet Muhammad SAW.From some of the conditions that exist in society on the understanding of "terrorists and Islam Nusantara" raises anxiety on academic researchers to seek answers on "Terrorism, Islam Nusantara and rahmatan lil'alamin."Nahdtlatul Ulama (NU) is the largest organization in Indonesia as a representation of Muslims. An understanding of terrorism, Islam and Islam Nusantara rahmatan lil 'Alamin will be extracted from the Branch Executive Nahdtlatul Ulama (PCNU) Cilacap.Researchers assume that; Nahdtlatul Ulama (NU) is a representation of Islam Nusantara that Branch Executive Nahdtlatul Ulama (PCNU) Cilacap also have an important role in preaching / called on Muslims to implement the teachings of Islam Nusantara for the realization rahmatan lil'alamin.This study is a qualitative research field, thus Researchers will use qualitative research methods with random sampling theory Milles accordance with the triangulation of data. While the idea is inductive qualitative groove.This Researchers can to know about Islam Nusantara is very nice, humbly, savety and so good to implemantion and aplication in the religious life and social relation in this country, many others and world. Islam Nusantara is true religion, that Islam from propet Muhammad SAW, not new Islam. So we must be recieved its.Keyword: Islam Nusantara, Nahdlatul Ulama, Peace